TEACHING AND INTEGRATING LANGUAGE SKILL (International Conference on Economics, Finance, Banking and Management, 2025)
Great topic -language skills are essential to effective communication and learning. When we talk about teaching and integrating language skills, we’re usually referring to the four core areas: